The Application of Field Trip Learning Method to Mangrove Forest as a Source of Geography Learning - Wahid Hasyim Asyari; Aris Munandar; Samadi Samadi (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
In this study, the aim was to determine differences in the results of student scores using the field trip learning method, both pretest and posttest on the field trip learning method. This study uses a quantitative research approach with a type of experimental research. This type of research is an experiment that uses the population in this study, class XI IPS SMAN 1 Sindang, ranging from XI IPS 1 to XI IPS 4, which consists of 144 students. However, the sample in this study is class XI IPS 1 and XI IPS 2, consisting of 36 students per class, totaling 72 student samples. The sampling technique carried out in this study is using purposive sampling techniques. The data collection method in this study is through test exam results conducted pretest and posttest in learning to see the difference in student scores by providing tests. In contrast, the data analysis technique used is the T-test analysis to see the difference in value results before and after being given online and offline field trip learning treatment. The data analysis technique used is the T-test analysis to see the difference in value results before and after being given online and offline field trip learning treatment. The results of this study were that there were differences in the learning outcomes of the control class and the experimental class both in the pretest and posttest; the control class in the pretest had an average score of 67.33, and after being given an offline field trip treatment, the average value increased to 79.89 while for the experimental class in the pretest had an average value of 65.61 and after being given an online field trip treatment the average value increased to 80.38. These two field trip learning methods can improve student scores, although, in this learning method, each has advantages and disadvantages.